PHARMACODYNAMICS OF DRUGS USED IN RHEUMATISM IN YOUNG CHILDREN - Abdurahmonov Ilhom Rustamovich (Journal of Science in Medicine and Life, 2024)
Rheumatism or acute rheumatic fever according to the International Classification of Diseases (ICD) is a systemic inflammatory disease of connective tissue with the main localization of the process in the cardiovascular system, and in people prone to it develops in connection with acute streptococcal infection. mostly 7-15 years old. Although not a common disease, rheumatism is a serious problem in cardiorheumatology due to the frequent formation of heart defects and the development of temporary and permanent disability. According to ICD-10, acute rheumatic fever is classified as a disease of the circulatory system (class IX) under the following codes: Rheumatism was known in the 5th century BC. Hippocrates wrote in his "Four Books of Diseases": "With arthritis, fever occurs, sharp pains grip all the joints of the body, and these pains sometimes die. sharper, sometimes weaker, affecting the first or other joints." In ancient times, doctors believed that inflammation in the joints was caused by some toxic fluid circulating throughout the body. The name of the disease comes from here - "rheumatism" (Greek "rheum" - flow). Damage to the cardiovascular system was considered a complication of articular syndrome. Only after the publication of the wonderful works of the French doctor Buyot (1836) and the Russian doctor IG. Sokolsky (1838), rheumatism was defined as an independent disease associated with heart damage.